Grant Dependence, Regulation and the Effects of Formula-based Grant Systems on German Local Governments: A Data Report for Saxony-Anhalt - Peter Haug (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2013)
Recent empirical studies have found - seemingly - efficiency-enhancing effects of vertical grants on local public service provision. The main purpose of this paper is to prepare an elaborate theoretical and empirical analysis of these contradictory results. Therefore, it investigates if certain fiscal and institutional conditions (fiscal stress, fiscal rank-preserving vertical grant systems, input- and output regulation), that might help to explain these empirical findings, are characteristic of at least some parts of the local government sector or certain regions. The German state of Saxony-Anhalt is chosen for case study purposes. The main results are: First, the local governments suffer from severe fiscal problems such as high grant dependency, low tax revenues and the prevalent inability to finance investments by own resources. Second, the output- and inputregulation density of certain mandatory municipal services (schools, childcare facilities, fire protection) is high. Finally, the most important vertical grant category for local governments, the formula-based grants ('Schlüsselzuweisungen'), can be described as mainly exogenous, unconditional block grants that in most cases preserve the relative fiscal position of the grant recipients. – – In einigen neueren empirischen Untersuchungen wurde ein - scheinbar - effizienzsteigernder Effekt von vertikalen Zuweisungen auf die kommunale Leistungserstellung festgestellt. Der vorliegende Beitrag stellt eine Vorstufe zu einer ausführlichen theoretischen und empirischen Analyse dieser widersprüchlichen Befunde dar. Zu diesem Zweck wird das Vorliegen bestimmter fiskalischer und institutioneller Rahmenbedingungen (Finanzschwäche, rangerhaltende vertikale Zuweisungssysteme, Input- und Outputregulierung), die möglicherweise zur Erklärung dieser Ergebnisse beitragen können, für Teile des kommunalen Sektors oder zumindest bestimmte Regionen untersucht. Das Bundesland Sachsen-Anhalt wird dazu als Fallstudie herangezogen. Die wesentlichen Ergebnisse sind: Erstens leiden die Kommunen unter schwerwiegenden fiskalischen Problemen wie ausgeprägter Abhängigkeit von Zuweisungen, niedrigen Steuereinnahmen und der weitverbreiten Unfähigkeit zur Eigenfinanzierung von Investitionen. Zweitens ist die Output- und Inputregulierungsdichte für bestimmte kommunale Pflichtaufgaben (Schulden, Kindertagesstätten, Brandschutz) sehr hoch. Schließlich lässt sich die für die Kommunen bedeutendste Kategorie der vertikalen Zuweisungen, die Schlüsselzuweisungen, als im Wesentlichen exogene, nicht-zweckgebundene Zuweisungen charakterisieren, die in den meisten Fällen die relative fiskalische Position der Zuweisungsempfänger nicht verändern.
urn:nbn:de:gbv:3:2-22417
Keywords: H71; H72; 330; vertical grants; local public finance; fiscal equalization; regulation of the public sector; Saxony-Anhalt; Vertikale Finanzzuweisungen; Kommunalfinanzen; Kommunaler Finanzausgleich; Regulierung des öffentlichen Sektors; Sachsen-Anhalt